1998
DOI: 10.1007/s001340050576
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombin III (ATILL) replacement therapy in patients with sepsis and/or postsurgical complications: a controlled double-blind, randomized, multicenter study

Abstract: The results of ATIII treatment in this population of patients suggests that replacement therapy reduces mortality in the subgroup of septic shock patients only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
109
1
5

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(119 citation statements)
references
References 23 publications
(28 reference statements)
4
109
1
5
Order By: Relevance
“…4,20,21 A theoretical limitation to the use of both UFH and LMWH in critically ill patients is driven by the low levels of antithrombin III that occur in sepsis thus reducing their therapeutic effectiveness, particularly in the case of UFH whose main mechanism of action is the high affinity to and activation of antithrombin III. 22,23 This can contribute to a shorter filter survival even when UFH anticoagulation level seems to be adequate, as indicated by targeted aPTT measurements. 24 Reported advantages of LMWH over other anticoagulants are easier administration (intermittent doses) due to their low affinity to plasma proteins, endothelial cells, and macrophages, larger bioavailability and a more predictable therapeutic effect not requiring laboratory monitoring of their antithrombotic activity.…”
Section: Discussionmentioning
confidence: 99%
“…4,20,21 A theoretical limitation to the use of both UFH and LMWH in critically ill patients is driven by the low levels of antithrombin III that occur in sepsis thus reducing their therapeutic effectiveness, particularly in the case of UFH whose main mechanism of action is the high affinity to and activation of antithrombin III. 22,23 This can contribute to a shorter filter survival even when UFH anticoagulation level seems to be adequate, as indicated by targeted aPTT measurements. 24 Reported advantages of LMWH over other anticoagulants are easier administration (intermittent doses) due to their low affinity to plasma proteins, endothelial cells, and macrophages, larger bioavailability and a more predictable therapeutic effect not requiring laboratory monitoring of their antithrombotic activity.…”
Section: Discussionmentioning
confidence: 99%
“…However, in sepsis‐induced DIC, a decrease in AT activity is frequently observed27, 28, 29, 30 and is associated with high mortality rates 31, 32. Several RCTs to investigate the effects of high‐dose AT administration in patients with sepsis have been carried out 4, 33, 34, 35, 36. Although some RCTs indicated benefits of high‐dose AT administration in patients with sepsis,33, 34, 35 a large RCT (the KyberSept trial) failed to show any survival benefits 4.…”
Section: Antithrombinmentioning
confidence: 99%
“…Several RCTs to investigate the effects of high‐dose AT administration in patients with sepsis have been carried out 4, 33, 34, 35, 36. Although some RCTs indicated benefits of high‐dose AT administration in patients with sepsis,33, 34, 35 a large RCT (the KyberSept trial) failed to show any survival benefits 4. However, a subgroup analysis of the KyberSept trial indicated that AT administration significantly improved survival rates in patients with sepsis‐induced DIC 9…”
Section: Antithrombinmentioning
confidence: 99%
“…60 Small clinical trials suggested improved survival rates in patients receiving rATIII. [61][62][63][64] Eisele et al 62 reported that rATIII therapy was associated with decreased lung dysfunction. However, Waydas et al 63 found no difference in the duration of organ failure.…”
Section: -22mentioning
confidence: 99%